2021
DOI: 10.1016/j.scitotenv.2021.146427
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the impact of variations of ambient air pollution and meteorological factors on lung cancer mortality in Yangtze River Delta

Abstract: Lung cancer (LC) mortality, as one of the top cancer deaths in China, has been associated with increased levels of exposure to ambient air pollutants. In this study, different lag times on weekly basis were applied to study the association of air pollutants (PM2.5, PM10, and NO2) and LC mortality in Ningbo, and in subpopulations at different age groups and genders. Furthermore, seasonal variations of pollutant concentrations and meteorological variables (temperature, relative humidity, and wind speed) were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Earlier studies corroborated this conclusion (Wang et al , 2019; Zhu et al , 2019). Chung et al (2021), Sloan et al (2012), and Wei et al (2020), on the contrary, observed the inverse. As according studies, the incidence of lung cancer was higher in the high-temperature group and the high-temperature group than in the low-temperature group (Guo et al , 2021).…”
Section: Discussionmentioning
confidence: 93%
“…Earlier studies corroborated this conclusion (Wang et al , 2019; Zhu et al , 2019). Chung et al (2021), Sloan et al (2012), and Wei et al (2020), on the contrary, observed the inverse. As according studies, the incidence of lung cancer was higher in the high-temperature group and the high-temperature group than in the low-temperature group (Guo et al , 2021).…”
Section: Discussionmentioning
confidence: 93%
“…In general, air pollutants are negatively associated with temperature, except for O 3 concentration level which is positively correlated to temperature ( 31 , 32 ). O 3 is a secondary pollutant generated by a series of photochemical reactions between precursors such as NO 2 and VOCs in the atmosphere.…”
Section: Air Pollution-related Disease Burden In Chinamentioning
confidence: 99%
“…Their study also provided the evidence in which the influences of NO 2 , O 3 , and SO 2 tend to be greater on the cool and dry days, which further highlighted that the effect of meteorological variables such as relative humidity could modify the impact of air pollutants on emergency COPD admissions ( 51 ). A study conducted in Yangtze River Delta reported that the LC mortality increased by 6.3, 4.1, and 4.6% for each 10 μg/m 3 increase in PM 2.5 , PM 10 , and NO 2 on a weekly basis, respectively, in the period of relative humidity less than 73.7% ( 32 ). Previous study has reported that greater effect of air pollution on allergic rhinitis, which is one of the allergic respiratory diseases, were observed at low temperature and high relative humidity ( 52 ).…”
Section: Air Pollution-related Disease Burden In Chinamentioning
confidence: 99%
“…Epidemiological studies show that if the average concentration of PM 2.5 increases by 10 μg·m −3 every two days, the daily cardiovascular mortality rate will increase by 0.36–1.22%, and the daily respiratory mortality increases by 0.74–1.78% [ 1 , 2 , 3 ]. If the weekly concentration of PM 2.5 increases by 10 μg·m −3 , the weekly total lung cancer mortality rate will increase by 6.2% [ 4 ]. PM 2.5 concentration is related to severe obstructive and chronic diseases of the respiratory and cardiovascular systems such as asthma and emphysema [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%